Characteristics and components of the Korean educational system - Al-Mutaqi, Maysam Abdullah; Al-Rubaish, Bayan Rashid (Journal of Educational and Psychological Sciences, 2022)
The objective of the study is to identify the general objectives of education in South Korea, to identify the factors affecting the education system in South Korea, to identify ways of financing education in South Korea, to identify the advantages of education in South Korea, and to access the benefits of South Korea’s educational experience in Saudi Arabia. Care, appreciation and importance of education for the individual and society, as well as strong adherence to their culture, including language, religion and social values, as well as attention to the preparation of teachers and the selection of distinguished persons for education, especially in the early stages of education.